2018
DOI: 10.1016/j.ygcen.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced brain expression of genes related to cell proliferation and neural differentiation is associated with cortisol receptor expression in fishes

Abstract: Stress enhances or inhibits neurogenesis in mammals and some fish species. The link between the two processes is still unclear. Most studies have been performed in very specific stressful or altered environments. Despite the known inter-individual divergence in coping abilities within populations, the relationship between the stress axis and neurogenesis has never been addressed in unstressed individuals. Here we correlate brain expression of the pcna (proliferating cell nuclear antigen) and neurod1 (neurogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Primer sequences were retrieved from the literature [45,63,64] or specifically-designed using the web version of PRIMER 3 (http://primer3.ut.ee; Table 1). The qPCR experiments were conducted in a final volume of 1.5 μl, using 1 μl fish brain cDNA and 0.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
See 2 more Smart Citations
“…Primer sequences were retrieved from the literature [45,63,64] or specifically-designed using the web version of PRIMER 3 (http://primer3.ut.ee; Table 1). The qPCR experiments were conducted in a final volume of 1.5 μl, using 1 μl fish brain cDNA and 0.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%
“…Recent studies suggest that stress axis regulation and neurogenesis are tightly linked [45][46][47].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it has been successfully applied by a variety of scientists, from physiologists (Auperin et al, ) to behavioural ecologists (Colson et al, ), in controlled environments and also in the wild (Geffroy et al, ; Love et al, ), to assess levels of stress in fishes. In addition, relation between the stress axis and neurogenesis (Sadoul et al, ; Sørensen et al, ), growth (Sadoul & Vijayan, ) and sex determination or sex‐change (Geffroy & Bardonnet, ; Goikoetxea et al, ; Olivotto & Geffroy, ) are now well described, highlighting the central role of cortisol in fish physiology and behaviour. It is also an important tool in characterising coping abilities of fishes and investigating how the environment can disturb this.…”
Section: Introductionmentioning
confidence: 99%
“…In sh, cortisol binds the glucocorticoid receptor (gr) and controls BDNF expression in the brain. With gr and relatively few other genes, BDNF has thus emerged as one of the target genes of interest in stress studies, as shown for zebra sh [134], sea bream [135] and sea bass [86,[136][137][138]. BDNF is also involved in other aspects of the stress response in sh (e.g.…”
Section: A Brain-derived Neutrophic Factor (Bdnf) Networkmentioning
confidence: 99%